Bat diversity in the Cuc Phuong National Park, Vietnam - Results from VIETBIO field training and annotated species list. - Sofía Hayden Bofill; Frieder Mayer; Vu Dinh Thong (Biodiversity Data Journal, 2024)
Biodiversity surveys are essential for both academic research and conservation. Integrative approaches that combine morphological, genetic and acoustic aspects for species identification can provide reliable information in taxonomy and evolution. This is especially relevant for those groups with a high degree of cryptic diversity such as bats.Here, we present the results from a field survey carried out in the Cuc Phuong National Park (CPNP) during 2019 as part of the VIETBIO project and from the examination of specimen collections preserved at the museums of CPNP and the Institute of Ecology and Biological Resources (IEBR). In addition, we include an annotated species list, based on this survey and a literature review. We here confirm that CPNP is home to at least 47 bat species belonging to 23 genera and seven families. We recorded ten of these bat species during our field survey. Obtained data in genetics (sequencing a fragment of the mitochondrial gene COI) supported the morphological identification of the recorded species for which we were able to produce these data. In addition, we include echolocation recordings obtained during our field training with the hope that they may contribute valuable insights to future work concerning the surveyed species. Results from the field survey represent a relevant contribution to biodiversity assessment efforts and, thus, support conservation and management efforts to maintain bat diversity in Vietnam.